Don't miss your train! Just follow the computer screen animation: Comprehension processes of animated pubic information graphics - Groff, J.; Boucheix, J.; Lowe, Richard; Argon, S.; Saby, L.; Alauzet, A.; Paire-Ficout, L. (Elsevier, 2013)
Computer graphic animated information displays have the potential to communicate public information in situations where normal announcement types are ineffective. This study used eye tracking techniques to analyze comprehension mechanism of event-related information on railway traffic disruptions presented via different graphic formats presented on computer screen. 86 participants were asked to understand series of traffic disruption messages delivered via four purely visual formats: Static simultaneous, Static sequential, Animated simultaneous and Animated sequential. Across these four conditions, and contrary to the most common materials used in the studies on animation comprehension, the sequentiality and the animated properties of the entities of the presentation were not confounded. Results revealed the Animated sequential displays were the most effective presentation type. Eye tracking data showed why an animation facilitates comprehension of public information graphics: it enhances processing strategies which provide the best condition for segmenting and composing the causal chain of the events provided in the message.